Cross-cultural adaption of the German Quebec Back Pain Disability Scale: an exposure-specific measurement for back pain patients - Riecke, Jenny (J Pain Res, 2016)
STUDY DESIGN: Cross-cultural translation and psychometric testing. OBJECTIVE: The purpose of the present study was to examine reliability and validity of a cross-cultural adaption of the German Quebec Back Pain Disability Scale (QBPDS) in a context of a randomized controlled trial evaluating the effectiveness of graded in vivo exposure in chronic low back pain patients. BACKGROUND: The QBPDS is one of the most widely used disease-specific disability questionnaires. In particular, for cognitive behavioral treatments with a clear focus on behavioral aspects such as graded in vivo exposure, the QBPDS provides an ascertained strategy with a sound conceptual basis and excellent quality criteria. Nevertheless, there is conflicting evidence concerning factor structure and a German adaption is missing. METHODS: The cross-cultural adaption followed international guidelines. Psychometric testing was performed using data from 180 participants with chronic low back pain. The psychometric analyses included internal consistency, convergent, and divergent validity. Exploratory factor analysis was used to determine the underlying factor structure. RESULTS: The QBPDS showed strong psychometric properties, with high internal consistency for the full scale (α=0.94) and good convergent and divergent validity. The factor analysis revealed a four-factor solution (bending, ambulation, brief effortful movements, and long-lasting postures). CONCLUSION: The translation and cross-cultural adaption of the QBPDS into German was successful. The German version proved to be a valid and reliable instrument and is well suited for use in the context of an exposure-based psychological treatment.